Thixotropic system based on mixture of hydrophilic and hydrophobic silica - V. V. Тurov; V. M. Gun'ko; T. V. Krupskaya; L. S. Andriyko; A. I. Marynin; V. N. Pasichnyi (Хімія, фізика та технологія поверхні, 2020)
Particles of hydrophilic (A-300) and hydrophobic (AM1) silicas, interacting with each other, form secondary structures in which the gaps between non-porous nanoparticles shape texture mesopores and macropores. Water addition to this system during the process of mechanochemical action results in a forming of composite system with thixotropic properties. Thus, the aim of the work was to study the phase state and parameters of the water binding to the surface of solid particles in systems consisting of two parts of hydrophilic and one part of hydrophobic silica with a variable water content. Using the methods of 1H NMR spectroscopy, electron microscopy, laser correlation spectroscopy and rheological studies, the state of water was studied, its thermodynamic parameters, as well as the  A-300/AM1 composite particle size distribution were determined. It has been found that water in the interparticle gaps of the A-300/AM1 composite is in the form of polyassociates similar to clusters and domains in liquid water. It was shown that with increasing water concentration (from 1 to 4 g/g) in the composite, its bulk density, the amount of strongly bound water and the total change in its free energy increased. It has been found that for composites with different hydration, similar clusters size distributions of adsorbed water are observed, where two maxima are identified at R = 5–7 and 20–30 nm, and most of the water is part of cluster structures with radius of 20–40 nm. It has been shown that a suspension based on of a mixture of 2/1 hydrophilic and hydrophobic silicas and 3 g/g of water, depending on the mechanical loading, can be in the state of a wet powder or viscous liquid, having high thixotropic properties, which are manifested in diluted aqueous suspensions. For dispersing of such a composite in an aqueous medium, aggregates form in with a diameter of 80–100 and 200–1000 nm, which indicates intense interparticle interactions. The interaction energy of the nanoparticles surface in the composite with the aqueous medium increases from 12 to 18 J/g with an increase in the water content from 1 to 4 g/g. Under the influence of shear load, the viscosity of the diluted suspension decreases by an order of magnitude, and then is restored at a level which exceeds the initial one almost at twice. It has been found that the obtained colloidal system is irreversible in the aqueous medium and under the mechanical load influence in the working cylinder of a viscometer, its viscosity characteristics intensify.